Applying Gagne's Events of Instruction in a Computer-Based Test Preparation Listening Material Design - Acmad Suyono (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2018)
The advances in computer technology have brought the rise of computer-based instructional materials in many different fields  including  language  learning.  With  regard  to  listening  skill  development,  one  obvious  strength  of  the  computer-based instructional materials is its capability of presenting audio component in various ways to improve students’ listening skill. For students who are preparing themselves to take a standardized test like Test of English as a Foreign Language (TOEFL), the materials can even be designed to provide a high degree of customization that can be geared specifically to meet students’ pace of learning. However, it can be a big challenge to design a computer-based listening material capable of ensuring that learning indeed takes place while the students are using and exploring its contents. This paper aims to propose the application of Gagne's nine events of instruction in a computer-based test preparation listening material design. More specifically, this paper tries to provide guidance in the process of developing the user interface and the content presentation within the material as to match each part of the nine events. It is expected that this strategy will successfully activate the required cognitive process of the students and help them achieve established learning objectives.